BEREDAY'S METHODOLOGICAL PROPOSAL FOR COMPARATIVE EDUCATION; COMMENTS AND POSSIBILITIES - Peixoto, Beatriz Ribeiro [UNESP]; Silva, Alexandre de Souza e; Rossetto Salotti, Luciana Siqueira (Unesp-faculdade Ciencias & Letras, 2021)
Comparative Education is a method of studying national educational systems arising at the end of the 18th century in Europe and arriving in Brazil at the end of the 19th century. The following article aims to describe the different approaches of some classical authors, and some commentators in the area, describing the views and collaborations of all of them for a better understanding of the theoretical and methodological elements of Comparative Education, as well as the various changes and influences on research methodology in the field of comparative studies, at different times in history. In this direction, this article approaches and discusses the contribution of Bereday, understood as one of the main authors of Comparative Education; and Bray and Thomaz, Novoa and Bonitatibus, as some of the most studied commentators on the methodology of Comparative Education, and the possible relationships between them.
Keywords: Comparative education; Research methodology; Educational systems